NOW OR NEVER: PUBLIC HEALTH ISSUES REQUIRING URGENT ATTENTION - Ulhaq, Intisar (Journal of Ayub Medical College Abbottabad, 2017)
Pakistanis a developing country and most of its population is based in rural areas. Over the last two decades’ significant changes have occurred in the health system in an attempt to improve the health care in general with a particular emphasis in the health of people living in rural areas. Despite these efforts, significant development and planning is required to improve the health of nation. Undoubtedly ministry of health has taken practical steps in tacking some serious health issues such as polio. However, the fact remains that there are a number of public health issues which if not addressed on an urgent basis, there is a great danger that the implications would be huge with unbearable consequences. Among various issues, only those are discussed here which are in a dire need of attention of government, ministry of health, department of public health, disaster management authorities, health education authorities, health institutions and health professionals. Keywords: Natural disasters; floods; Earthquakes; snake bite; dog bite; burns; antenatal; postnatal; neonatal; mortality; morbidity;road traffic accidents; deaths; health education